Flexural Strengthening of Self-Compacting Reinforced Concrete L-Shaped Columns with Carbon Fiber: Experimental Study - Hamad , Ziyad A.; Yaseen, Sinan A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
Reinforced concrete (RC) columns are fundamental structural elements in buildings responsible for transferring loads from superstructures to the foundations. Improving their performance under different load conditions is important for ensuring structural safety and long-term durability, particularly to increase the flexural strength of columns. Because carbon fiber-reinforced polymer (CFRP) composites are so strong, lightweight, corrosionresistant, and simple to install, they should be used instead of traditional strengthening methods. This study examines the flexural strengthening of self-compacting RC L-shaped columns under axially and biaxially eccentric loads by using longitudinally applied CFRP. Six cases of columns in total were prepared and tested, including three unstrengthened columns and three flexurally strengthened with CFRP, which were tested at eccentricities (ex = ey ) of 0 mm (pure axial load), 50 mm, and 100 mm. The experimental findings showed that various loading conditions led to different failure processes. While concentrically loaded specimens failed suddenly as a result of brittle concrete crushing and reinforcement bar buckling, columns subjected to eccentric loading showed combined flexural-compression failure characterized by tension-side cracking, lateral displacement, and compression-side concrete crushing. There is less impact on increasing axial capacity at (ex = ey = 0), with an improvement of roughly 6%. The load capacity improved by up to 27% at (ex = ey = 50 mm) and 39% at (ex = ey = 100 mm) under eccentric loading. Results show loading situations have a major impact on the performance of CFRP, with flexural improving moment capacity, ductility, and fracture control under eccentric loads.